2006
DOI: 10.1117/12.666267
|View full text |Cite
|
Sign up to set email alerts
|

Visual suppression of monocularly presented symbology against a fused background in a simulation and training environment

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…We have shown previously that visibility was reduced for a monocularly viewed alphanumeric character under partial fusion conditions similar to those we will describe here, but only with static imagery and at a fixed contrast. 28 In the present study, we examine the effect of motion (flight over terrain) and target contrast on the visibility of monocularly viewed symbology. …”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that visibility was reduced for a monocularly viewed alphanumeric character under partial fusion conditions similar to those we will describe here, but only with static imagery and at a fixed contrast. 28 In the present study, we examine the effect of motion (flight over terrain) and target contrast on the visibility of monocularly viewed symbology. …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that our study included simple BR conditions with one rivalrous stimulus to each eye, while in operational aircraft the graphical information is often presented to one eye only while both view, and binocularly fuse, the same out-the-window scene. It is known that BR is less under these latter conditions [22].…”
Section: Discussionmentioning
confidence: 97%
“…It may be that eye-dominance and rivalry do not play a significant role in performance until viewing conditions are more degraded. Previous research 13 showed that for low contrast monocular targets presented briefly, performance was degraded when compared to binocularly viewed targets. Further, this effect has been shown to disappear when target contrast is increased from 10% to 40% 14 .…”
Section: Discussionmentioning
confidence: 98%